Assessing variation in physicochemical, structural, and functional properties of root starches from novel Tanzanian cassava (Manihot esculenta Crantz.) landraces. (20th January 2016) - Mtunguja, Mariam K.; Thitisaksakul, Maysaya; Muzanila, Yasinta C.; Wansuksri, Rungtiva; Piyachomkwan, Kuakoon; Laswai, Henry S.; Chen, Guihua; Shoemaker, Charles F.; Sinha, Neelima; Beckles, Diane M.
Abstract : Cassava is an ideal "climate change" crop valued for its efficient production of root starch. Here, the physicochemical properties and functionality of starches isolated from six cassava landraces were explored to determine how they varied from each other and from those previously described, and how they may be potentially used as value‐added foods and biomaterials. Among genotypes, the parameters assayed showed a narrower range of values compared to published data, perhaps indicating a local preference for a certain cassava‐type. Dry matter (30–39%), amylose (11–19%), starch (74–80%), and reducing sugar contents (1–3%) differed most among samples ( p  ≤ 0.05). Only one of the six genotypes differed in starch crystallinity (41.4%; while the data ranged from 36.0 to 37.9%), and mean starch granule particle size, (12.5 μm instead of 13.09–13.80 μm), while amylopectin glucan chain distribution and granule morphology were the same. In contrast, the starch functionality features measured: swelling power, solubility, syneresis, and digestibility differed among genotypes ( p  ≤ 0.05). This was supported by partial least square discriminant analysis, which highlighted the divergence among the cassavas based on starch functionality. Using these data, suggestions for the targeted uses of these starches in diverse industries were proposed.